Nurses’ Knowledge Regarding Chest Tube Management in Tertiary Level Hospital of Chitwan, Nepal - Shrestha, Mamata; Sapkota, Sandeep; Thakur, Binay (Nepalese Journal of Cancer, 2025)
Background: A chest tube insertion is a common procedure in which chest tube is inserted through the side of the chest into the pleural space in order to drain the pleural cavity of air, blood, pus or lymph. Nurses’ having sufficient knowledge and experience contributes to the acceleration of the recovery process of the patients and the reduction of potentially fatal complications. This study focuses to assess nurses’ knowledge regarding care of patients undergoing chest tube and to find some relevant associations. Methodology: A descriptive analytical study was carried out among 88 nurses selected using convenience sampling technique who were working in Intensive Care Units, Surgical and Operational Departments of B.P. Koirala Memorial Cancer Hospital. The data were collected by using Self-administered questionnaire. Statistical evaluation was calculated using IBM SPSS v20 program. Descriptive statistics (mean, standard deviation, frequency, percentage, etc.) and inferential statistics (chi square test) were calculated in the evaluation of the data. Results: Findings of the present study showed that more than half (56.8%) nurses had moderate knowledge regarding management of patients with chest tube. While 40.9% and 2.3% nurses had good and poor knowledge, respectively. There was no significant association between level of knowledge regarding chest tube management and selected socio-demographic variables such as age(p=0.195), education(p=0.323), job experience(p=0.487), guidelines (p= 0.316). Many nurses (40%) relied on peer discussions as their source of knowledge which reveals a gap, as informal sharing cannot substitute structured, evidence-based training programs. Formal training regarding chest tube management was not received by any participants. Only 27.3% participants had read the necessary guidelines. Conclusion: The majority of the studied nurses had moderate knowledge regarding management of patient with chest tube without getting sufficient training opportunity. Nurses’ knowledge was mostly based on unreliable sources rather than evidence-based guidelines or sources.